2017
DOI: 10.1016/j.tate.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge relations and epistemic infrastructures as mediators of teachers' collective autonomy

Abstract: This paper examines how teachers' knowledge relations and the profession's epistemic infrastructure shape collective autonomy. Professionals' autonomy derives partially from their responsibility for a specific knowledge base. This responsibility is currently challenged by educational policies and complex knowledge landscapes. Existing research has shown how epistemic policy instruments impact teachers' autonomy. However, less attention has been paid to how professional autonomy is informed by teachers' knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 69 publications
0
21
0
3
Order By: Relevance
“…When combining online and campus activities, integrating digital resources, a critical area requiring further discussion and research is the understanding of how online communities and resources function (Harasim, 2012), and the analytical work required to adapt and interpret the potential of these resources for use in local settings' (Hermansen, 2017: 2). Findings from the cycles described contribute to this missing research area (Harasim, 2012;Hermansen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When combining online and campus activities, integrating digital resources, a critical area requiring further discussion and research is the understanding of how online communities and resources function (Harasim, 2012), and the analytical work required to adapt and interpret the potential of these resources for use in local settings' (Hermansen, 2017: 2). Findings from the cycles described contribute to this missing research area (Harasim, 2012;Hermansen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that school leaders historically have distanced themselves from the teachers by developing a role as professional bureaucrat or administrator (Scheerens 2012;Mehta 2013). If school leaders identify with the administration, administrative knowledge and ethos prevail in schools (Mehta 2013) where teachers' professional knowledge base is weak (Hermansen 2017). A possible countermove on the accountability reform movement is, therefore, to intelligently strengthen the teaching profession through closer connecting teachers, school leaders, and researchers through dialogues about what is important in schools and how this can be practiced and assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The paper takes its theoretical point of departure in the sociology of knowledge as applied to educational research. Here, we find arguments for the insufficiency of instrumentalism (Hermansen & Nerland, 2014, p. 190) and a blueprint for understanding school leadershipas well as other professional practicesas knowledge work, carried out in the interplay of policy, organization and professional practice (Hermansen, 2017). This paper researches leadership conversations as a form of knowledge work.…”
Section: Theoretical Framework Knowledge Responsibility and Epistemmentioning
confidence: 93%
“…The paper aims to make this complex situation open for analysis by thinking of standards of organization and assessment data as examples of epistemic objects (Knorr Cetina, 2001;Nerland & Jensen, 2012). Epistemic objects are 'conceptual and material artefacts' (Hermansen, 2017) characterized by a level of constancy or objectcharacter, such as in the case of this paper, assessment tools that support practical school leadership (that is, directed at solving complex problems) by providing a research-based knowledge foundation (Halverson & Kelley, 2017). It is a key theoretical claim of this paper that epistemic objects play a key role in the organization of professional practice, because they provide orientation in the complex realities of professional work.…”
Section: Theoretical Framework Knowledge Responsibility and Epistemmentioning
confidence: 99%